CO2 Laser Cutting of Glass Fiber Reinforce Polymer Composite - M., Ishak; Fatimah, S.; S. N., Aqida (IOP Publishing, 2012)
The lamination, matrix properties, fiber orientation, and relative volume fraction of matrix of polymer structure make this polymer hard to process. The cutting of polymer composite using CO2 laser could involve in producing penetration energy in the process. Identification of the dominant factors that significantly affect the cut quality is important. The objective of this experiment is to evaluate the CO2 spot size of beam cutting for Glass Fiber Reinforce Polymer Composite (GFRP). The focal length selected 9.5mm which gave smallest focus spot size according to the cutting requirements. The effect of the focal length on the cut quality was investigated by monitoring the surface profile and focus spot size. The beam parameter has great effect on both the focused spot size and surface quality.